(untitled) - Dhiman, Anil Kumar (Darya Ganj, New Delhi, 2003)
Contents of material: Introduction. Computer basics. Harware-Computer. Software-Computer. Data communication and networking. Internet: Basics and tools.
Keywords: Library science,Information technology